I'm not, like, the best dragon, ya know?: A Deconstructionist Reading of Disney’s Raya and the Last Dragon - Subekti, Adaninggar Septi (ProTVF, 2024)
Background: Raya and the Last Dragon is the first Disney movie inspired by traditional Southeast Asian cultures, somewhat under-represented in mainstream media. Hence, the movie is worth further investigation. Purpose: The study intends to read Disney’s Raya and the Last Dragon using a deconstructionist lens. Methods: The study used qualitative analysis of audio-visual materials. The auditory and visual aspects of the movie are examined using a deconstructionist lens by watching and rewatching the movie with occasional note-taking. Data are presented in the forms of characters’ dialogues, and screen captures of relevant scenes. Results: It found that, to a certain extent, the movie deconstructs dominant narratives. The most prosperous tribe, Heart’s chief, chooses to promote trust and cooperation over violence. Then, against popular views associating toddlers with innocence, this movie presents a toddler as a con baby. It also seems to advocate the power of youngsters to make a difference in society. Though it seems to have feminist details through its two androgynous female warriors, Raya and Namaari, the same characters lead Kumandra to its downfall and eventual rise. It suggested that female warriors can achieve great things but also bring catastrophes. The movie, furthermore, portrays Sisu as an insecure yet trusting dragon, quite different from the typical portrayals of dragons often associated with power and destruction. However, the movie marginalizes the antagonists, the Druun, by not giving them the language to defend themselves from the judgmental assumptions of the talking characters. Implications: The movie carries hidden messages and could be used to challenge dominant narratives. It, however, could also be used to marginalize certain groups.